Identification of therapeutically potential targets and their ligands for the treatment of OSCC - Kumari, Pratima; Kumar, Sugandh; Sethy, Madhusmita; Bhue, Shyamlal; Mohanta, Bineet Kumar; Dixit, Anshuman (Frontiers in Oncology, 2022)
The variation in drug response has raised many questions considering the therapeutic potential and the right choice of drug used. It is important to identify the genetic basis of the drug efficacy and the limiting factors. Predicting the course of drug response aids in the determination of drug effectiveness and resistance issues. Therefore, it is imperative to identify the factors associated with therapeutic response to improve the outcome of chemotherapy. It will also lead to new-targeted therapy. In the current work, we have identified drug-specific sensitivity related prognostic biomarkers (BOP1, CCNA2, CKS2, PLAU, and SERPINE1) using gene expression, coxph-regression, and machine learning in oral squamous cell carcinoma (OSCC). Dysregulation of these markers is significantly associated with overall survival (OS) in many cancers. Their elevated expression is related to cellular proliferation and aggressive malignancy in various cancers. Mechanistically, inhibition of these biomarkers should significantly reduce the cellular proliferation and metastasis in OSCC and should result in better OS. It is pertinent to note that no effective small molecule candidate has been identified against these biomarkers to date. Therefore, a comprehensive in-silico drug design strategy assimilating homology modeling, extensive molecular dynamics (MD) simulation (500 ns), and ensemble molecular docking has been applied to identify potential compounds against identified targets and potential molecules have been identified. We hope this study will help in deciphering potential genes having roles in chemoresistance and significant impact on OS. It will also result in the identification of new targeted therapeutics against OSCC.